Business Analysis and Improvement of Import Container Dwelling Time Using DMAIC Methodology: Case Study of Berlian Terminal, Tanjung Perak Surabaya - Fadila Rusman, Denia; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2016)
Abstract. Ports are maritime transport infrastructure that have an important role in the economic structure and the mobility of goods, services, and people. As the primary node in the shipping system, port should be able to ensure smooth logistics activities and the contribution of material flows, products and information in the effective and efficient supply chain with low Dwelling Time. But what happened to Berlian Terminal, Tanjung Perak Surabaya is the high rate of Dwelling Time of import container that reached 8.4 days compared to the 5-day Dwelling Time in Thailand, 4-day in Malaysia and in Singapore was only 1 day. The purpose of this final project is to provide improvement solution that needs to be done by Terminal Berlian. This is done by analyzing the import container process when the container arrive at the port for unloading until they get out from the port. This method is expected to reduce the number of Dwelling Time and improve the service system in Terminal Berlian. The conceptual framework of this final project is based on the DMAIC Methodology by analyzing the business issue, then defining, measuring, analyzing, improving, controlling, and implementing based on plan. The root cause is because the total time of service procedures in Berlian Terminal is high which occurs on document and container services. The data were collected by doing survey on the field, interview, documentation, and collected from people that have been previously processed.The analysis process was done by providing 3 alternatives. The first alternative is analyzing the queue system in Berlian Terminal which is still good because there is no queue in the system . The second alternative is improving SOP on Pre Clerance process that can reduce the dwelling time up to 24%. The third alternative is chosen as the best alternative which combines the result in alternative 2 with SOP improvement on Red Lane Customs Clearance. The result shows that import container dwelling time can be reduced by 38% , from 8.4 days to 5.2 days. The reduction is expected to provide better service system for the importers, customs, and Berlian Terminal as a service provider company. The process of implementation plan can be done by defining the problem, resources plan, stakeholder agreement, improvement, and evaluation. To ensure the success of implementation business, the company should conduct Critical Success Factors and policies based on companyâ€™s vission and mission.Â Keywords : Dwelling Time, Vessel Queuing System, Pre Clearance, Customs Clearance, Post Clearance, Berlian Terminal, Import Container.